Cultural barriers to public administration reform: Results of an empirical study - Hensel, Przemysław (Journal of Public Governance, 2012)
The paper is based on an opinion survey of 1 217 Polish public administration employees, which was conducted in order to asses cultural determinants of the successful introduction of the New Public Management and the New Public Governance reforms. The results show that Polish public administration employees are not very eager to accept the implementation of competitive mechanisms in their workplace, and that they prefer solutions rooted in the hierarchical logic. It was concluded that factors positively affecting the probability of successful reforms are: the level of trust, which is higher among them than among the general public, and high awareness of the present dismal state of the administration. The opinions shared by the public administration employees were also compared with those expressed by the general population; regional differences in opinions were also analyzed.